Prenatal nicotine exposure enhances the susceptibility to metabolic syndrome in adult offspring rats fed high-fat diet via alteration of HPA axis-associated neuroendocrine metabolic programming - Xu Dan; Xia Li-ping; Shen Lang; Lei You-ying; Liu Lian; Zhang Li; Magdalou Jacques; Wang Hui (Acta Pharmacologica Sinica, 2016)
Aim: Prenatal nicotine exposure (PNE) alters the hypothalamic-pituitary-adrenocortical (HPA) axis-associated neuroendocrine metabolic programming in intrauterine growth retardation offspring rats. In this study we aimed to clarify the susceptibility to metabolic diseases of PNE offspring rats fed a high-fat diet. Methods: Maternal Wistar rats were injected with nicotine (1.0 mg/kg, sc) twice per day from gestational day 11 until full-term delivery, and all pups were fed a high-fat diet after weaning and exposed to unpredictable chronic stress (UCS) during postnatal weeks 18–20. Blood samples were collected before and after chronic stress, and serum ACTH, corticosterone, glucose, insulin, total cholesterol, triglyceride and free fatty acids levels were measured. The hypothalamus, pituitary gland and liver were dissected for histological studies. Results: UCS significantly increased the serum ACTH, corticosterone and insulin levels as well as the insulin resistant index without changing the serum glucose, total cholesterol, triglyceride and free fatty acids levels in adult offspring rats without PNE. The body weight of PNE offspring rats presented a typical “catch-up” growth pattern. PNE not only aggravated the UCS-induced changes in the HPA axis programmed alteration (caused further increases in the serum ACTH and corticosterone levels), but also significantly changed the glucose and lipid metabolism after UCS (caused further increases in the serum glucose level and insulin resistant index, and decrease in the serum free fatty acids). The effects of PNE on the above indexes after UCS showed gender differences. Pathological studies revealed that PNE led to plenty of lipid droplets in multiple organs. Conclusion: PNE enhances not only the HPA axis, but also the susceptibility to metabolic diseases in adult offspring rats fed a high-fat diet after UCS in a gender-specific manner and enhances the susceptibility to metabolic diseases in adult offspring rats fed a high-fat diet.